Epidemiological analysis of hydrometra and its predictive value in gynecological tumors - Wu, Jianfa; Wang, Sihong; Zhang, Li; Wu, Suqin; Liu, Zhou (Frontiers in Oncology, 2023)
Hydrometra is a common gynecological disease, especially in postmenopausal women. However, its epidemiological situation, harmfulness and predictive value in gynecological tumors have not been clearly recognized. In this study, 3903 women who participated in gynecological diseases screening at Zhoupu Hospital in Shanghai from 2021/01/01 to 2021/12/31 were employed to investigate the prevalence rate and risk factors of hydrometra. Moreover, another 186 patients with sonographic diagnosis of hydrometra in Zhoupu Hospital from 2020/01/01 to 2021/12/31 who underwent hysteroscopy and postoperative pathological examination were employed to study pathological distribution and predictive value in gynecological tumors. The observed prevalence rate of hydrometra was 10.86%, which was higher than other gynecological diseases. Univariate and multivariate analysis indicated that advanced age or vaginitis was independent risk factor for hydrometra (OR=1.11 ＆ OR=3.18). Of 186 patients with sonographic diagnosis of uterine fluid, it was finally revealed that simple hydrometra accounted for 34.41%; inflammation accounted for 16.23%; hemometra accounted for 2.15%, while gynecological tumor accounted for 5.91%. Moreover, univariate and multivariate analysis indicated that higher BMI index (>23.92), higher hydrometra volume (distance between the two layers of endometrium>4.75mm) and abnormal vaginal bleeding were high-risk predictive factors for gynecological tumors. In conclusion, hydrometra is a common disease, which is a risk factor for endometrial cancer and cervical cancer, especially with higher hydrometra volume, higher BMI and abnormal vaginal bleeding. It is necessary to pay more attention to hydrometra.